No association between postmenopausal time and the prevalence of newly discovered asymptomatic intracranial atherosclerotic stenosis: The APAC study. (August 2020) - Fan, Changfeng; Zhang, Qian; Wang, Anxin; Zhang, Xiaoli; Zhao, Xingquan
Highlights: Postmenopausal time is not an independent risk factor of AICAS. Vigorous control of body weight is vital for preventing the occurrence of AICAS. Blood pressure/glucose/lipids and smoke are risk factors of AICAS. Abstract: Introduction: Asymptomatic intracranial atherosclerotic stenosis (AICAS) is a common cause of stroke. Elderly women were more likely than men to develop AICAS, although it indicated that a lifelong exposure to estrogen could lower the risks of cardiovascular disease (CVDs). Objective: The present study aims to ascertain whether postmenopausal time is a risk factor of AICAS. Fostering a correct perception of menopause is of great significance for the overall well-being of the elderly women. Methods: All participants received a questionnaire, physical examination, laboratory testing and transcranial Doppler. The menopausal population (n = 701) was divided into three groups by tertiles of postmenopausal time. Two-tailed testing and trend test were used to reveal the relationship between postmenopausal time and newly discovered AICAS. Other potential risk factors were also analyzed to ascertain whether there was a relation between postmenopausal time and the newly discovered ICAS. Results: Both mean age and mean postmenopausal time were gradually increased from G0 to G2. The same trend occurred in hypertension, diabetes mellitus, total cholesterol, triglyceride, C-reactive protein and serum homocysteine. Adjusting for various confounding factors, postmenopausal time was not a risk factor for newly discovered AICAS. Multifactor analysis and stratifying analysis showed no correlation between newly discovered AICAS and postmenopausal time. Conclusions: Postmenopausal time is not an independent risk factor of AICAS. No relationship was detected between postmenopausal time and newly discovered AICAS, while vigorous control of body weight, blood pressure/glucose/lipids and smoke cessation are vital for preventing the occurrence of AICAS.